The White Muslim Converts in Australia: Socio-Religious Reality and Identity Formation - Sukarma, Sukarma; Farah, Rafika Rabba (Jurnal Dakwah Risalah, 2023)
Conversion is not only observed as a theological change in someone’s belief and behavior, but  socio-cultural change that affects identity formation. This present study is conducted qualitatively involving ten Muslim converts who are associated with the white Western people. It aims at investigating their identity formulation on the process of becoming and being Muslims in the Western context in Australia, Sydney especially. Also, this research is to find the comparison between male and female converts’ identity formation.Results show that social challenge has the biggest part of the Muslim converts’ identity formation. Further, the study pictures different pattern of social challenges between male vs male and male vs female Muslim converts that leads to their identity formation. This study has highlighted that Muslim converts in the Western context have been challenged more by the socio-religious reality than faith-related practices. This study suggests that the Muslim community and the born Muslim family living in Australia are encouraged to set a program to address this tension.